(untitled) (Studia Prawnicze / The Legal Studies, 1985)
The author says that every theory of law is connected with a certain theory of language and, that is why, the theory and philosophy of law are interested in such notions as “discursion” and "text”. The author analyzes instrumental and noninstrumental concepts of language and legal discursion. He speaks in favour of noninstrumental approach which makes it possible to criticize that discursion. The he asks a question: in what conditions of deconstruction of Western metaphysics the illusion of legal discursion may be transformed into real mythology of culture.